A probabilistic reliability assessment for transmission development planning in the Philippine restructured power industry - Lagrada, Rey M. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
The current practice in ensuring the acceptable power transmission reliability level in transmission development planning in the Philippines is based on the single outage contingency (N-1 redundancy) criterion. The application of probabilistic approach in assessing transmission reliability can enhance the current deterministic methods. This paper illustrates the application of probabilistic reliability assessment to the Philippine power grid by using the state enumeration method. The method starts with the formulation of alternatives to address transmission problems. Then, the Expected Energy Not Supplied (EENS) of each proposed options is evaluated using the forced outage rates of the transmission facilities. The total cost of each alternative which is mainly comprised of capital investment, operation and maintenance, and unreliability costs are determined. The alternative having the least total cost is selected as the best option. In this study, the developed models and methodology for probabilistic reliability assessment was applied to the Mindanao transmission development plan. It was shown that there is an alternative that can meet the acceptable reliability level but entails the least cost among other proposed alternative and projects of NGCP (National Grid Corporation of the Philippines).
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Electric power transmission -- Reliability; Reliability (Engineering) -- Mathematical models; Electric power transmission -- Philippines